Prevalence of Varroa destructor Infestations in Apis mellifera Honeybee Colonies and Associated Risk Factors in Ankasha District, Northwest Ethiopia - Aschalew Shitu Yenew; Yodit Ayalew Sisay (Veterinary Medicine and Science)
ABSTRACT Background Varroa destructor is an ectoparasite of broods and adult stages of honeybees, which gradually leads to colony losses worldwide, both directly (feeding on fatty tissue) and indirectly (disease transmission). Objectives The objectives of this study were to determine the prevalence of varroosis and to identify possible risk factors for the occurrence of varroosis. Methods The honeybee colonies were selected by a simple random sampling method from each apiary of 90 volunteer apiarists. Combs containing mature drone broods were taken out of each colony and examined for the presence of V. destructor on the brood and in the cell. A cross‐sectional study design was used for data collection. The data were analysed by chi‐square test (χ2) and logistic regression. Results Overall, 66.15% of honeybee colonies were infested with V. destructor. Colony strength, colony age and agro‐ecology had statistically significant (p < 0.05) associations with the occurrence of varroosis. Weak colonies were 4.89 (p < 0.001) times more likely to be at risk to varroosis than moderate colonies. Likewise, honeybee colonies with the age of 2–3 years and >3 years were 1.99 and 4.74 (p < 0.001) times more likely to be at risk to varroosis than colonies with <2 years, respectively. Furthermore, honeybee colonies in highland and midland agro‐ecologies were 3.67 and 5.07 (p < 0.001) times more likely at risk to infestation of varroosis when compared with colonies from lowland agro‐ecologies, respectively. Conclusion Varroosis is prevalent in the study area, which alarms the starting of an effective control option to save honeybee colonies.